Intrathecal Hydromorphone and Morphine for Postcesarean Delivery Analgesia: Determination of the ED90 Using a Sequential Allocation Biased-Coin Method. Issue 1 (March 2017) - Sviggum, Hans P.; Arendt, Katherine W.; Jacob, Adam K.; Niesen, Adam D.; Johnson, Rebecca L.; Schroeder, Darrell R.; Tien, Michael; Mantilla, Carlos B.
Abstract : ( Anesth Analg. 2016;123:690–697) The gold standard for pain control is intrathecal (IT) morphine, with an optimal dose for postcesarean analgesia ranging from 0 to 500 μg. However, there have been national shortages of preservative-free morphine, and dose-dependent opioid-induced side effects (nausea, pruritus, sedation, and respiratory depression) do occur. IT hydromorphone is a potential alternative for providing postcesarean analgesia. The authors of the present study thus identified dosages of IT hydromorphone that provided effective analgesia in 90% (ED90 ) of patients.